2024
DOI: 10.3390/nu16091288
|View full text |Cite
|
Sign up to set email alerts
|

Roseburia intestinalis Supplementation Could Reverse the Learning and Memory Impairment and m6A Methylation Modification Decrease Caused by 27-Hydroxycholesterol in Mice

Xuejing Sun,
Cui Zhou,
Mengwei Ju
et al.

Abstract: The abnormality in N6-methyladenosine (m6A) methylation is involved in the course of Alzheimer’s disease (AD), while the intervention of 27-Hydroxycholesterol (27-OHC) can affect the m6A methylation modification in the brain cortex. Disordered gut microbiota is a key link in 27-OHC leading to cognitive impairment, and further studies have found that the abundance of Roseburia intestinalis in the gut is significantly reduced under the intervention of 27-OHC. This study aims to investigate the association of 27-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…The gut microbiota changes with age, affecting gut barrier function and regulating cognitive abilities through the gut brain axis 49 . Francesco Marotta revealed that age-related changes in gut microbiota composition include a decrease in microbial diversity, a decrease in dominant species abundance, and an increase in sub dominant species abundance 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota changes with age, affecting gut barrier function and regulating cognitive abilities through the gut brain axis 49 . Francesco Marotta revealed that age-related changes in gut microbiota composition include a decrease in microbial diversity, a decrease in dominant species abundance, and an increase in sub dominant species abundance 50 .…”
Section: Discussionmentioning
confidence: 99%